Low-Intensity Extracorporeal Shock Wave Therapy Ameliorates the Overactive Bladder: A Prospective Pilot Study. (7th July 2020) - Lee, Yung-Chin; Chuang, Shu-Mien; Lin, Kun-Ling; Chen, Wei-Chiao; Lu, Jian-He; Chueh, Kuang-Shun; Shen, Mei-Chen; Liu, Li-Wen; Long, Cheng-Yu; Juan, Yung-Shun
Abstract : Objective . In the present clinical trial, we evaluated the therapeutic effects of low-intensity extracorporeal shockwave therapy (LiESWT) on overactive bladder (OAB). Methods . Female subjects with ages of 20-75 years and who have been clinically diagnosed with OAB were included in the study. The LiESWT (DUOLITH SD1 T-TOP, AG) applicator was placed on the suprapubic skin area and applied with an intensity of 0.25 mJ/mm 2, 3000 pulses, and 3 pulses/second. To assess the therapeutic efficacy, all subjects were required to complete the validated OAB symptoms and life bothersome questionnaires, 3-day urinary diary, uroflowmetry, and post-voided residual urine (PVR) measurement at 4 weeks of LiESWT (W4), 8 weeks of LiESWT (W8), 1-month follow-up (F1), and 3-month follow-up (F3) after LiESWT. Result . 82 subjects with the mean age of 56.5 ± 1.2   years were enrolled. The questionnaire scores were significantly improved at W4, W8, F1, and F3 as compared to baseline data (W0). At W8, the mean values of functional bladder capacity were meaningfully increased. According to the 3-day urinary diary, daytime frequency, urgency, and nocturia were significantly decreased. The uroflowmetry results showed that the mean voided urine volume and the maximal flow rate (Q max ) were noticeably increased. PVR volume was also significantly decreased. Conclusions . The data demonstrated that 8-week LiESWT ameliorated the OAB symptoms, promoted the uroflow parameters, and improved the quality of life (QoL) in OAB patients, suggesting that LiESWT might serve as an alternative noninvasive therapy for OAB.